Is the Tourism Business Ready to Face the Threat of Tsunami Disaster? (Case Study of Coastal Area of North Lombok Regency) - Rumambi, Freddy Johanis; Sari, Dwi Novita (Department of Urban and Regional Planning, Diponegoro University, 2023)
Due to its proximity to the Flores Back Arc Thrust, North Lombok Regency, a popular tourist location in Indonesia, is regarded as being particularly vulnerable to earthquakes with the potential to trigger tsunamis. Concrete steps must be taken to lower the risk of a tsunami's impact and safeguard the stability of the tourism sector. This study aimed to find out how the preparedness of the tourism business in the coastal area of North Lombok Regency in facing the threat of a tsunami disaster by looking at the aspects of preparedness are a) Vulnerability Assessment b) Planning; c) Institutional Framework; d) Information System; e) Resource Base; f) Warning System; g) Response Mechanisms; g) Education and Training; and h) Rehearsal. The type of case study research with a qualitative approach was chosen in this study. The respondents involved consisted of tourism business actors whose information was extracted using in-depth interview techniques, focus group discussions, and observation. The Miles and Huberman model was used to assess the data once it was obtained, and data triangulation was used to reduce bias. The study's findings indicated that raising awareness of the tourism industry is still necessary, and that the industry's post-tsunami preparedness is only limited to the creation of standard operating procedures and the installation of evacuation routes. The need for integrated cooperation between tourism businesses, the government and the community in maximizing effective and efficient preparedness.